2003
DOI: 10.1074/jbc.m301830200
|View full text |Cite
|
Sign up to set email alerts
|

Altered Balance of Half-reactions in p-Hydroxybenzoate Hydroxylase Caused by Substituting the 2′-Carbon of FAD with Fluorine

Abstract: Apo-p-hydroxybenzoate hydroxylase was reconstituted using 2-fluoro-2-deoxy-arabino-FAD, a synthetic flavin in which the hydroxyl of the 2-center of the ribityl chain was replaced with fluorine in an inverted configuration. The absorbance spectral changes caused by the binding of either p-hydroxybenzoate (pOHB) or 2,4-dihydroxybenzoate (2,4-diOHB) indicated that the isoalloxazine of the artificial flavin adopts the more solvent-exposed "out" conformation rather than the partially buried "in" conformation near t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(38 reference statements)
2
2
0
Order By: Relevance
“…3B). This is consistent with the formation of flavin hydroperoxide, which typically exhibits a 10–15 nm blue shift [35,36]. This blue shift takes place in the red to the cyan transition ( k CD in Fig.…”
Section: Resultssupporting
confidence: 83%
“…3B). This is consistent with the formation of flavin hydroperoxide, which typically exhibits a 10–15 nm blue shift [35,36]. This blue shift takes place in the red to the cyan transition ( k CD in Fig.…”
Section: Resultssupporting
confidence: 83%
“…1), revealing a role for the 2′‐OH position of the flavin ribityl side chain in maintaining the correct geometry of a key active site residue. Interestingly, only a few studies have so far explored the role of the flavin side chain in flavoenzymes [25–29] and our results support its importance also in Fcb2.…”
Section: Resultssupporting
confidence: 82%
“…Flavin analogs modified in the ribityl side chain may also provide insight into flavoprotein function and mechanism [54,84–87]. For medium‐chain acyl‐CoA dehydrogenase, it was shown that the replacement of natural FAD by 2′‐deoxy‐FAD reduces the activity of the enzyme about a millionfold [84].…”
Section: Flavin Analogsmentioning
confidence: 99%